Regional studies on silkworm cross-breeding behavior - Abreu, Oldemar C.; Bonilha, Nivaldo A.; Abramides, Pedro; Souza, Celso F. de; Marques, Lúcia M. Queiroz (Pesquisa Agropecuaria Brasileira, 2014)
The results of comparisons of six silkworm crosses, conducted at the Rio de Janeiro State Experiment Station in cooperation with the Instituto de Pesquisas e Experimentação Agropecuárias do Centro-Sul, are presented. Two series of trials were made: one in the spring and the other during the summer. In the spring trials cross IS.116 x IS.120 and IS.120 x IS.116 were superior to the other crosses. In the summer trials crosses IS.116 x IS.120 were superior to all others. For production of silk the spring production of crosses IS.118 x IS.117 and IS.117 x IS.118 was best. Superiority was measured by cocoon production and weight.